Mitigating school dropout among deaf learners through school support networks: case study - Makatse, Mapulane Cecilia (University of the Free State, 2021)
School dropout phenomenon is a world-wide problem affecting all students including Deaf learners and other learners with special educational needs. Regardless of all the attempts made, school dropout among deaf learners (hereafter - DL), still remain a challenge within our schools, as compared to their hearing counterparts. Therefore this study explored how school support networks could be used to mitigate school dropout among deaf learners in a selected high school in Leribe District in Lesotho through school support networks perceived to be available within and outside the school. Based on positive psychology, a strength-based theory was used to guide the study. The study followed the qualitative approach and adopted the transformative paradigm, also utilising a participatory research design. Focus group discussions and collages were the methods employed by the researcher to generate data from nine deaf learners who were purposefully selected through the help of an interpreter. Thematic analysis was adopted. The findings are that the deaf learners possessed a diverse understanding of school support networks and viewed them as both human and non-human support networks, found within and outside the school environment. Furthermore, the findings showed diverse ways employed by the identified school support networks to mitigate school dropout among deaf learners, being provision of academic support, proffering emotional and psychosocial support, as well as providing social support that shaped their learning and enabled them to interact with others and have a sense of belonging. The result also identified resources used by Deaf learners, such as computer and resource rooms, library and playgrounds, etc., which supported them to achieve their academic goals. The study concluded that deaf learners’ academic success is everyone’s responsibility and through school support networks all stakeholders can collaborate and enhance opportunities for all deaf learners to become compatible community members.
Dissertation (M.Ed. (Psychology of Education))--University of the Free State, 2021
Keywords: Mitigating; Dropout; Deaf learners; School support networks; Collage; Focus group